Fasciola hepatica Control Practices on a Sample of Dairy Farms in Victoria, Australia - Kelley, Jane M.; Rawlin, Grant; Beddoe, Travis; Stevenson, Mark; Spithill, Terry W. (Frontiers in Veterinary Science, 2021)
In Australia, little is known about strategies used by farmers to control Fasciola hepatica (F. hepatica) infection in dairy cattle. Triclabendazole- resistant F. hepatica have recently been found on several dairy and beef properties in Australia. It is difficult to draw conclusions about how widespread resistance is in Australian dairy cattle because we have little information about flukicide usage, drug resistance testing and alternative flukicide usage on-farm. This study's objective was to determine how dairy farmers are currently controlling F. hepatica and to identify knowledge gaps where F. hepatica control strategies need to be communicated to farmers to improve management. The survey was distributed online or by hardcopy and 36 dairy farmers completed the survey. There were 34 questions including closed, open-ended, multi-check box, demographic and text questions. Descriptive statistics were used to quantify each response. The survey results showed high use of clorsulon, limited rotation of flukicides and limited use of diagnostic tests to inform treatment options and timing. There was poor adherence to best management practice in determining the dose of flukicides administered to cattle, with farmers often relying on estimating body weights or average body weights, suggesting that underdosing of animals is likely to be prevalent. Most respondents in this study did not isolate and quarantine treat newly returned or purchased animals before joining them with the main herd. The research identified four knowledge gaps where communication needs to be enhanced to improve control of F. hepatica: diagnostic testing to inform flukicide use, rotation of flukicide actives, flukicide administration and increased testing of replacement animals.